Characteristics of occupational pesticide poisoning in agricultural workers treated at the Hospital Barranca Cajatambo during 2008 – 2017 - Cruz Aquino, Lincol Marx (2019)
Objective: To determine the characteristics of occupational pesticide poisoning in agricultural workers treated at the Hospital Barranca Cajatambo during 2008-2017. Materials and methods: A descriptive, retrospective and cross-sectional study conducted in a population of 295 agricultural workers poisoned by occupational pesticide exposure and treated at the Hospital Barranca Cajatambo from 2008 to 2017. Every male or female agricultural worker aged over 14 with a complete medical record of pesticide poisoning was included in the study. The variables were the sociodemographic and epidemiological characteristics of the pesticide and intoxication. Absolute frequencies (n) were used for the qualitative variables and relative frequencies (%) for the relative variables. Measures of central tendency (average) and dispersion tendency (standard deviation) were used for the quantitative variables. Data was processed using software SPSS v25.0 and presented in simple tables. Results: Ninety-eight percent (98.0 %) of the study subjects were males, 47.5 % were between 15 and 25 years, 53.6 % were single, 68.1 % had secondary education, 67.5 % worked as pesticide applicators, 56.9 % had a normal BMI, and 97.6 % presented no comorbidities. Pesticides were classified as fungicide (39.7 %), herbicide (37.6 %), organophosphorus (98.0 %) and moderately toxic (96.3 %). The routes of entry to the body were the airways (57.3 %) and skin (42.0 %). In relation to poisoning, the time between pesticide exposure and arrival to the hospital ranged from 1 to 3 hours (53.9 %). The severity of poisoning was moderate (94.2 %). The most frequent clinical manifestations were vomiting (79 %) and nausea (72.5 %). Treatment included IV medication (99.7 %) and atropine (81.7 %). Ninety-nine point three percent (99.3 %) of the study population progressed with no hospital- cquired complications. Finally, 100 % of the patients improved their health condition at discharge. Conclusions: Most agricultural workers poisoned by pesticides were young, male and single; had secondary education; worked as pesticide applicators; did not present comorbidities; and had a normal BMI. The most frequently used pesticides were fungicides, herbicides, those moderately toxic and those entering the body through the airways. Poisoning was moderate with no hospital-acquired complications. The present study evaluates the short-term effects of pesticide poisoning in agricultural production. It is necessary to take into account its long-term effects such as cancer and neurological conditions. In this regard, the government should review the policy related to reducing the production and application of pesticides.